What Every Neuropathologist Needs to Know: Peripheral Nerve Biopsy. Issue 4 (18th March 2020) - Chkheidze, Rati; Pytel, Peter
Abstract: Peripheral neuropathy is a common disorder with many possible etiologies including metabolic diseases, inflammatory conditions, infections, malignancy, inherited diseases, drugs, and toxins. In most instances, diagnosis and treatment plan can be established based on clinical presentation, family history, laboratory results, genetic testing, and electrophysiological studies. But in some situations, a peripheral nerve biopsy remains a valuable tool. This is especially true in patients with rapidly progressive disease, with atypical presentation or for whom other approaches fail to yield a definitive diagnosis. The pathologic examination starts with basic decisions about specimen triage. A few basic questions help to provide an initial framework for the assessment of a nerve biopsy—is the specimen adequate; are there inflammatory changes; are there vascular changes; is there amyloid; are there changes to axonal density and the Schwann cell-myelin-axon unit. In the appropriate context and with such an approach peripheral nerve biopsies can still represent a clinically helpful test.